A model‐based analysis to guide gonadotropin‐releasing hormone receptor antagonist use for management of endometriosis. Issue 5 (13th January 2022) - Pohl, Oliver; Baron, Kyle; Riggs, Matthew; French, Jonathan; Garcia, Ramon; Gotteland, Jean‐Pierre
Abstract : Aims: To identify linzagolix doses, an oral GnRH receptor antagonist, that effectively lower oestradiol (E2) to relieve endometriosis‐related pelvic pain without compromising bone health. Methods: Integrated statistical, pharmacokinetic–pharmacodynamic and systems pharmacology models were developed from Phase 1 and 2 clinical trial data in healthy volunteers and patients, receiving linzagolix 25–200 mg daily or placebo, and analysed simultaneously. The main outcome measures were pelvic pain scores for dysmenorrhoea, nonmenstrual pelvic pain (NMPP), uterine bleeding and lumbar spine bone mineral density (BMD). Results: Linzagolix pharmacokinetics were described by a 2‐compartment model with sequential zero/first‐order absorption process (CL/F: 0.422 L/h). E2 changes over time were well described as a function of linzagolix 24‐hour AUC (AUC50 : 1.68 × 10 5 ng h/mL). For a Caucasian reference patient, a change in E2 from 50–20 pg/mL at 24 weeks increased the odds of relief of dysmenorrhoea 1.33‐fold and NMPP 1.07‐fold (95% CI: 1.22–1.47 and 1.02–1.12, respectively) and decreased bleeding days by 1.55 (95% CI: 1.39–1.72). A previously validated quantitative systems pharmacology BMD model was adjusted to the clinical data. The mean week 24 lumbar spine BMD change from baseline ranged from −0.092% in the 50 mg dose, −1.30% in the 100 mg dose group and −2.67% in the 200 mg dose group. Discussion: The previously‐reported E2 target range (20–50 pg/mL) to balance efficacy and safety endpoints was confirmed. Linzagolix once daily doses between 75–125 mg daily were expected to meet endometriosis‐associated pain, efficacy, and BMD loss targets in Caucasian patients.